Differential coupling of m-cholinoceptors to Gi/Go-proteins in failing human myocardium - Mittmann, Clemens; Pinkepank, Gunnar; Stamatelopoulou, Sophia; Wieland, Thomas; Nürnberg, Bernd; Hirt, Stefan; Eschenhagen, Thomas (Journal of molecular and cellular cardiology, 2003)
Muscarinic acetylcholine receptors (mAChRs) mediate their main cardiac effects via pertussis toxin-sensitive G-proteins. Physiological effects differ considerably between atrium and ventricle, and it is unknown to which extent these differences derive from selective receptor-G-protein coupling or further downstream events. We have characterized specific coupling between mAChRs and Gi/Go-protein isoforms in atrial and ventricular myocardium by agonist-dependent photoaffinity labeling with [(32)P]azidoanilido GTP (aaGTP) and immunoprecipitation in sarcolemmal membranes from terminally failing human hearts. The total amount of mAChRs, as determined by specific binding of [(3)H]QNB, was significantly higher in right-atrial (RA +/- SEM, 959 +/- 68 fmol/mg, n = 4) than in left-ventricular membranes (LV, 582 +/- 53 fmol/mg, n = 6). Standardized immunoblots revealed that Gialpha-2 was the predominant subtype in both regions. A 40-kDa splice variant of Goalpha (Goalpha-1 and/or Goalpha-3) was almost exclusively detectable in RA. Levels of Gialpha-3 and a 39-kDa splice variant of Goalpha (Goalpha-2) were also higher in RA. Basal aaGTP binding was higher in RA than in LV for all Gialpha/Goalpha subtypes. The carbachol (10 micromol/l)-induced increase in aaGTP binding was significantly higher in RA than in LV for Goalpha-1/3 (336 +/- 95% of LV, n = 4) and for Gialpha-3 (211 +/- 83%), lower for Gialpha-2 (42 +/- 5%), and was similar in both regions for Goalpha-2 (130 +/- 62%). The differential coupling of mAChRs in human RA and LV suggests that the initiation of different physiological responses to mAChR stimulation starts with signal sorting at the receptor-G-protein level.
Gesehen am 07.04.2022